ANALISIS FAKTOR PENYEBAB KESALAHAN PELAFALAN KATA BAHASA INGGRIS PADA SISWA KELAS III SDN 09 KOTO BARU - Lutfiah, Zumrotun; Atika Putri, Dhara; Yunara, Rayendra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low English vocabulary pronunciation ability of third-grade students at SD Negeri 09 Koto Baru. The students still experienced difficulties in pronouncing English vocabulary, particularly vowel and consonant sounds, tended to pronounce words based on Indonesian spelling, and lacked confidence in speaking English. This study aimed to describe the factors affecting the English vocabulary pronunciation ability of third-grade students at SD Negeri 09 Koto Baru. The study employed a qualitative approach using a descriptive method. Data were collected through observations, interviews, and documentation, and were analyzed through data reduction, data display, and conclusion drawing. The trustworthiness of the data was ensured through source triangulation, technique triangulation, and member checking. The findings revealed that students’ English vocabulary pronunciation ability was influenced by both internal and external factors. The internal factors included students’ age, learning interest, learning motivation, and self-confidence. Meanwhile, the external factors included mother tongue interference, the habit of using Indonesian in daily communication, limited family support and pronunciation practice, the social environment, and the teaching methods and learning media used by the teacher External factors were found to be the most dominant because students had limited opportunities to hear and practice English pronunciation outside the school environment. Therefore, continuous pronunciation practice, support from both families and schools, and the use of varied teaching methods and learning media are needed to improve students’ English pronunciation ability.